Biallelic Mismatch Repair Deficiency in an Adolescent Female - Amber Hildreth; Mark A. Valasek; Irene Thung; Thomas Savides; Mamata Sivagnanam; Sonia Ramamoorthy; Sherry Huang (Case Reports in Genetics, 2018)
Constitutional (Biallelic) Mismatch Repair Deficiency is a rare autosomal recessive disorder characterized by numerous cancers presenting as early as the first decade of life. Biallelic germline variants in one of four mismatch repair genes (MLH1, MSH2, MSH6, or PMS2) cause this devastating disease. Given the rarity of the syndrome, often-asymptomatic tumors, and overlap with neurofibromatosis-1, diagnosis is frequently unrecognized or delayed. We present a unique case of a 14-year-old female with minimal gastrointestinal symptoms diagnosed with invasive adenocarcinoma secondary to biallelic PMS2 variants.